Exile in Language - Peter Baker (Studies in 20th & 21st Century Literature, 1990)
Saint-John Perse's poem Exil (1941) represents a deep meditation on the nature of "writing" as subsequent critical theory has developed that term. Though the poem seems to present a "signature" at the end, it may be that the poet through giving in to a radically different signifying practice is in some sense not the signatory of the text. The archaic setting and difficult-to-resolve cultural matrix from this perspective become means of examining the co-originary origins of thought and language. Close analysis of textual patterns reveals a composition practice based on anagrammatic patterning. This kind of questioning of language in the practice of the text drives out all other characters and even the subjectivity of the presumed speaking subject. Exil is thus an exile in language that causes its readers to re-examine structures of interiority and exteriority on which identity and culture are based.
Keywords: Saint-John Perse; Exil; nature of writing; critical theory; petry; sign; thought; language; anagrammatic patterning; enteriority; exteriority; identity; culture